The book of teeth and bones - Okazaki, Masayuki (Cambridge Scholars Publishing, 2021)
This book will be very valuable for people suffering from teeth and bone diseases and students aiming to become either dentists or doctors. Bones regenerate, but teeth do not, once they are damaged. This is exactly why dental materials are needed, though, of course, it would be best if they did not have to be used in the first place. Unfortunately, it is impossible to create artificial teeth exactly the same as natural teeth using today's dental materials and technology. As such, it is very important to pay attention to the teeth and routinely take good care of them if people do not want to regret the loss of their teeth in their old age. This book introduces the reader to the world of apatites used to compose teeth and bones. It will boost their interest in biomaterials, and improve their understanding about the daily efforts of dentists, dental technicians, and hygienists.